1997
DOI: 10.1073/pnas.94.16.8509
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of a peroxisomal Ca 2+ -dependent member of the mitochondrial carrier superfamily

Abstract: A cDNA from a novel Ca 2؉ -dependent member of the mitochondrial solute carrier superfamily was isolated from a rabbit small intestinal cDNA library. The full-length cDNA clone was 3,298 nt long and coded for a protein of 475 amino acids, with four elongation factor-hand motifs located in the N-terminal half of the molecule. The 25-kDa N-terminal polypeptide was expressed in Escherichia coli, and it was demonstrated that it bound Ca 2؉ , undergoing a reversible and specific conformational change as a result. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 61 publications
(51 reference statements)
0
49
0
Order By: Relevance
“…The wide distribution of APCs in the eukaryotic kingdom indicates that this transporter plays an important role that has been conserved throughout evolution. The rabbit protein named Efinal (accession number AF004161), which is an ortholog of APC1 with 87% similarity, has been reported to have a peroxisomal location (40), which contrasts with the mitochondrial localization of the human APCs shown here. This discrepancy may be due to a low specificity of the anti-Efinal antibody used, which indeed displays immunoreactivity both at peroxisomal and mitochondrial levels (40).…”
Section: Influence Of Membrane Potential and Ph Gradient On The Apc-mmentioning
confidence: 41%
See 3 more Smart Citations
“…The wide distribution of APCs in the eukaryotic kingdom indicates that this transporter plays an important role that has been conserved throughout evolution. The rabbit protein named Efinal (accession number AF004161), which is an ortholog of APC1 with 87% similarity, has been reported to have a peroxisomal location (40), which contrasts with the mitochondrial localization of the human APCs shown here. This discrepancy may be due to a low specificity of the anti-Efinal antibody used, which indeed displays immunoreactivity both at peroxisomal and mitochondrial levels (40).…”
Section: Influence Of Membrane Potential and Ph Gradient On The Apc-mmentioning
confidence: 41%
“…The rabbit protein named Efinal (accession number AF004161), which is an ortholog of APC1 with 87% similarity, has been reported to have a peroxisomal location (40), which contrasts with the mitochondrial localization of the human APCs shown here. This discrepancy may be due to a low specificity of the anti-Efinal antibody used, which indeed displays immunoreactivity both at peroxisomal and mitochondrial levels (40). Consistently with our results, the rat protein (accession number NM_145677) that is an ortholog of APC3 with 85% similarity has recently been found to be localized to mitochondria (49).…”
Section: Influence Of Membrane Potential and Ph Gradient On The Apc-mmentioning
confidence: 41%
See 2 more Smart Citations
“…The subcellular localization of animal and plant UCPs is strongly suggested by their primary structure and the presence of the signature of mitochondrial carriers (see above), although it was reported that certain proteins of this family may be present in peroxisomes [80]. In the case of UCP1, the localization in mitochondria was demonstrated by functional assays, immunodetection and purification.…”
Section: Mitochondrial Localization Of the Ucpsmentioning
confidence: 99%